Walasuji Sulapa Eppa’na: Integrating Philosophical Values into Sustainable Development in the Land of To Kaili - Saleh, Muhammad; Mulyati, Ahda; Sirajuddin, Zaenal (Advances in Social Sciences Research Journal, 2025)
Walasuji - Sulapa Eppa'na is a cultural symbol of the Bugis-Makassar ethnic group in South Sulawesi, rich in philosophical values that embody spirituality, identity, mutual cooperation, and human responsibility in preserving nature. Its geometric pattern, composed of stacked quadrilaterals resembling rhombuses, serves not only as an aesthetic ornament but also symbolises the human journey towards perfection and the relationship with God. This concept represents the four main elements of life: God, humanity, the sky, the earth, and everything within it. However, in the Palu Valley, with the history of Bugis-Makassar ethnic migration, these philosophical values have begun to degrade due to globalisation, acculturation of forms, materials, functions, preferences, and the younger generation’s diminishing understanding of their ancestral traditions. As a result, Walasuji - Sulapa Eppa'na has become increasingly rare in the wedding ceremonies of the Bugis-Makassar-Kaili ethnic community, known as “To Kaili.” This research employs a qualitative method by exploring a single phenomenon, which is then analysed descriptively to understand the degradation of the cultural symbol Walasuji - Sulapa Eppa'na. The research objects are users of Walasuji structures, with Sulapa Eppa'na samples selected using purposive and incidental sampling techniques. The study aims to analyse the impact of changes on the preservation of Walasuji - Sulapa Eppa'na and explore the potential revitalisation of its values in urban development. The findings reveal that despite the degradation, the Bugis-Makassar-Kaili ethnic community continues to strive to preserve their cultural identity, including the responsibility of safeguarding nature. This study recommends integrating the values of Walasuji - Sulapa Eppa'na into urban development to achieve sustainable development.